Anterior “beaded” emulsification as a late complication of heavy silicone oil in retina surgery - Zewar, MBBS, FRCS, Ahmed N.; Lochhead, FRCOphth, Jonathan (Digital Journal of Ophthalmology, 2021)
We report 2 cases of emulsified silicone oil with a “beaded” appearance adherent to the posterior capsule as a long-term complication of heavy silicone oil tamponade in retina surgery. One case demonstrated mobile beaded opacity that has not been described in the literature previously. This heavy silicone oil complication might cause symptoms similar to posterior capsular opacity. Nd:YAG posterior capsulotomy can be considered as a treatment.